2015
DOI: 10.1111/jace.13587
|View full text |Cite
|
Sign up to set email alerts
|

Reduction‐Induced Inward Diffusion and Crystal Growth on the Surfaces of Iron‐Bearing Silicate Glasses

Abstract: We investigate the sodium inward diffusion (i.e., sodium diffusion from surface toward interior) in iron containing alkalineearth silicate glasses under reducing conditions around T g and the induced surface crystallization. The surface crystallization is caused by formation of a silicate-gel layer first and then the growth of silica crystals on the glass surface. The type of alkaline-earth cations has a strong impact on both the glass transition and the surface crystallization. In the Mg-containing glass, a q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…First, we focus on the effects of Mg. It is well established that the Mg coordination number (CN) (4, 5, or 6) changed discontinuously according to the field strengths of competing modifier cations in silicate glasses. Previous work indicated that the molar ratio of R + (alkali ions):Mg 2+ should have an important effect on the CN of Mg. Further systematic investigations indicated that the CN of Mg should be controlled by the average field strength of modifier cations.…”
Section: Discussionmentioning
confidence: 99%
“…First, we focus on the effects of Mg. It is well established that the Mg coordination number (CN) (4, 5, or 6) changed discontinuously according to the field strengths of competing modifier cations in silicate glasses. Previous work indicated that the molar ratio of R + (alkali ions):Mg 2+ should have an important effect on the CN of Mg. Further systematic investigations indicated that the CN of Mg should be controlled by the average field strength of modifier cations.…”
Section: Discussionmentioning
confidence: 99%
“…As is known, different types of alkaline‐earth ions have different abilities to attract the nonbridging oxygen (NBO) in glass, depending on the ion size. With substituting small alkaline‐earth ions for big ones in glass, the field strength ( F ) increases, that is, FSr2+<FCa2+<FMg2+, and hence, the ability of the alkaline‐earth ion to attract NBO increases in the same order 26 . As a consequence, the number of bridging oxygens per network forming cation (Si 4+ and Al 3+ ) rises and thus the structural network gets more connected.…”
Section: Resultsmentioning
confidence: 99%
“…It is worth mentioning here that apart from their own role changing (modifier ↔ former) behavior, TM cations also change the structural role of alkali cations. For instance, change in oxidation state of iron from Fe 3+ to Fe 2+ causes Na + and K + ions to change their role from charge balancers to network modifiers [19,20]. As a combined effect of these factors, diffusion of ions into each other during sintercrystallization is affected and variety of morphology is observed in the present samples due to variety of mixed valance states of corresponding TM ions.…”
Section: Densification and Morphologymentioning
confidence: 86%